The Automated and Electric Vehicles Act 2018 Part 1 and Beyond: A Critical Review. (31st October 2019) - Marson, James; Ferris, Katy; Dickinson, Jill
Abstract: On 19 July 2018, the Automated and Electric Vehicles Act 2018 (AEVA) received Royal Assent. As motor vehicles are becoming increasingly technologically based, with driving aids having taken over many of the more mundane (and possibly dangerous) aspects of driving from the driver, it is imperative that legislation keeps pace to determine the responsibilities of the parties. Motor insurance provides protection for those involved with vehicles and who may suffer harm, injury, and loss due to the negligence of the actors. This is most frequently driver error, but may also include manufacturing defects, which result in deaths and less serious injuries. It is also here where the intersection between torts and insurance laws needs careful management. It would be particularly unfair to ask drivers or third-party victims of motor vehicle accidents to seek redress from a manufacturer for losses incurred during the actions of an autonomous vehicle. Consumer law has historically removed this burden from affected consumers and it is entirely sensible for the law to protect individuals in an emerging field—and perhaps even more so given the trajectory of vehicles with driver-enabled qualities and the numbers of vehicles currently featuring such innovations. Yet, the AEVA consists of aspects which are troubling in respect of the motor insurance industry's dominance of this market, the application of compulsory insurance, and exclusions and limitations to responsibility which expose policy holders and victims to EU-breaching levels of risk.